The relationship between language features and PTSD symptoms: a systematic review and meta-analysis - Yu, Zhenyuan; Gu, Zixin; Shen, Yonghong; Lu, Jingbo (Frontiers in Psychiatry, 2025)
ObjectiveThe aim of this study is to investigate the relationship between language features and symptoms of Post-Traumatic Stress Disorder (PTSD) to determine if language features can serve as a reliable index for rapid screening and assessing PTSD.MethodsA comprehensive literature search was performed using Pubmed, Embase, Cochrane Central Register of Controlled Trials, Web of Science, and Ovid databases, augmented by backward reference tracking, to gather pertinent literature concerning language features and traumatic stress disorders published until August 2024.ResultsTwelve observational studies were included, comprising a cumulative sample size of 5,706 cases. Various language analysis tools, such as Linguistic Inquiry and Word Count (LIWC), manual coding, and machine learning techniques, were employed in the studies. Meta-analysis findings revealed a positive correlation between death-related words and PTSD symptoms (OR 1.32, 95%CI 1.10 to 1.59, I² 79.4%, p = 0.004), as well as significant positive correlations between negative emotion words and PTSD symptoms (OR 1.21, 95%CI 1.11 to 1.32, I² 30.5%, p < 0.001), anger-related words and PTSD symptoms (OR 1.14, 95%CI 1.11 to 1.17, I² 0.0%, p < 0.001), word count and PTSD symptoms (OR 1.20, 95%CI 1.09 to 1.31, I² 11.2%, p < 0.001). Additionally, a positive correlation was observed between body-related words and hyperarousal symptoms of PTSD (OR 1.26, 95%CI 1.15 to 1.37, I² 0.0%, p < 0.001), intrusive symptoms (OR 1.40, 95%CI 1.16 to 1.68, I² 0.0%, p < 0.001), and avoidance symptoms (OR1.29, 95%CI 1.21 to 1.37, I² 0.0%, p < 0.001). Death-related words (OR 1.16, 95% CI 1.08 to 1.25, I² 0.0%, p < 0.001) and word count (OR 1.18, 95% CI 1.10 to 1.27, I² 0.0%, p < 0.001) were observed positive correlations between intrusive symptoms of PTSD. Conversely, no correlation was found between the use of words related to sadness, anxiety, positive emotions, first-person pronouns, sensory, cognitive-related words and PTSD symptoms.ConclusionDeath-related words, anger-related words, negative emotion words, body-related words and word count in Language features hold promise as a reliable indicator for rapid screening and assessing PTSD; however, further research is warranted to investigate their relationship with PTSD symptoms across various cultural contexts, genders, and types of trauma.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO, identifier CRD42024528621.